Tackling mantle cell lymphoma (MCL): Potential benefit of allogeneic stem cell transplantation - Satish Shanbhag (Dove Medical Press, 2010)
Satish Shanbhag1,2, Mitchell R Smith1, Robert VB Emmons21Department of Medical Oncology, Fox Chase Cancer Center, 2Division of Bone Marrow Transplantation, Temple University, Philadelphia, PA, USAAbstract: Mantle cell lymphoma (MCL) is a type of non-Hodgkins lymphoma (NHL) associated with poor progression-free and overall survival. There is a high relapse rate with conventional cytotoxic chemotherapy. Intensive combination chemotherapy including rituximab, dose intense CHOP- (cyclophosphamide-doxorubicin-vincristine-prednisone) like regimens, high dose cytarabine, and/or consolidation with autologous stem cell transplant (autoSCT) have shown promise in significantly prolonging remissions. Data from phase II studies show that even in patients with chemotherapy refractory MCL, allogeneic stem cell transplant (alloSCT) can lead to long term disease control. Most patients with MCL are not candidates for myeloablative alloSCT due to their age, comorbidities, and performance status. The advent of less toxic reduced intensity conditioning (RIC) regimens, which rely more on the graft-versus-lymphoma (GVL) effect, have expanded the population of patients who would be eligible for alloSCT. RIC regimens alter the balance of toxicity and efficacy favoring its use. Treatment decisions are complicated by introduction of novel agents which are attractive options for older, frail patients. Further studies are needed to determine the role and timing of alloSCT in MCL. Currently, for selected fit patients with chemotherapy resistant MCL or those who progress after autoSCT, alloSCT may provide long term survival.Keywords: mantle cell lymphoma, allogeneic SCT, nonmyeloablative, GVL